2013
DOI: 10.1159/000356297
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Remnant Liver Hypertrophy Ratio after Preoperative Portal Vein Embolization

Abstract: Background: Portal vein embolization (PVE) is considered to improve the safety of major hepatectomy. Various conditions might affect remnant liver hypertrophy after PVE. The aim of the present study was to clarify the factors that affect remnant liver hypertrophy and to establish a prediction formula for the hypertrophy ratio. Methods: Fifty-nine patients who underwent preoperative PVE for cholangiocarcinoma (39 patients), metastatic carcinoma (10 patients), hepatocellular carcinoma (8 patients), and other dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 49 publications
(40 reference statements)
3
29
0
1
Order By: Relevance
“…Depending on various factors, such as the degree of liver cirrhosis and pretreatment with hepatotoxic chemotherapy, the volume of the FLR should be at least 20-40% of the total liver volume in order to be eligible for surgery (TLV) [3][4][5]. The degree of hypertrophy (DH) of the FLR after PVE also varies greatly between patients, and several studies have developed approaches to predict FLR growth based on laboratory values and clinicopathologic data, such as bilirubin levels and history of previous chemotherapy or liver surgery [6,7]. Recently, sarcopenia, the degenerative loss of skeletal muscle mass and function [8], has been shown to correlate with morbidity and mortality after major liver surgery and has been shown to adversely affect the outcome in various other severe diseases as well [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on various factors, such as the degree of liver cirrhosis and pretreatment with hepatotoxic chemotherapy, the volume of the FLR should be at least 20-40% of the total liver volume in order to be eligible for surgery (TLV) [3][4][5]. The degree of hypertrophy (DH) of the FLR after PVE also varies greatly between patients, and several studies have developed approaches to predict FLR growth based on laboratory values and clinicopathologic data, such as bilirubin levels and history of previous chemotherapy or liver surgery [6,7]. Recently, sarcopenia, the degenerative loss of skeletal muscle mass and function [8], has been shown to correlate with morbidity and mortality after major liver surgery and has been shown to adversely affect the outcome in various other severe diseases as well [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it would be interesting to compare these observations with those in other models such as carbon tetrachloride-induced liver injury model as we have done using mice [38]. The approach adopted in this study is considered to be applicable to the search for biomarkers of liver regeneration not only after PHx but also after preoperative portal vein embolization [41], and after associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) surgery [42], and therefore, we cautiously plan to conduct clinical trials and elucidate biomarkers for clinical use in our subsequent work.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported factors predictive of liver regeneration following PVE, such as pre-PVE FLR volume,[20, 29] receipt of chemotherapy,[33] and functional hepatic reserve. [33, 34] However, their analyses were based on the hypertrophy rate of the FLR (increase of FLR/pre-PVE FLR).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported factors predictive of liver regeneration following PVE, such as pre-PVE FLR volume,[20, 29] receipt of chemotherapy,[33] and functional hepatic reserve. [33, 34] However, their analyses were based on the hypertrophy rate of the FLR (increase of FLR/pre-PVE FLR). In contrast, we investigated predictors including administration of 2-stage hepatectomy based on DH (increase of standardized volume of S2+3) and KGR (DH at first assessment/time elapsed since PVE) because these kinetic profiles are able not only to evaluate the trophic effects of PVE but also to predict postoperative morbidity and mortality after major hepatectomy.…”
Section: Discussionmentioning
confidence: 99%